Analysis of the current state of housing construction sector in Kazakhstan - Baimbetova, А. А. (Journal of Economic Research & Business Administration, 2015)
Since independence, the Republic of Kazakhstan housing was one of the priorities of the National Development Strategy to 2030 and is one of the most important tasks of the national character. To date, the housing industry is implementing a program of housing construction in the Republic of Kazakhstan for 2011 - 2014 years. The Programme 2011 - 2014 established the basic principles and directions of housing - housing the local executive bodies to implement using savings system by funding and second-tier banks to finance the construction, continued construction of rental housing and the development of engineering infrastructure, as well as incentives to attract private investment in housing. The article provides an analysis of the real estate market of Kazakhstan. Determined that for the formation and steady development of the industry construction industry depends largely on the state policy in the field of investment, the introduction of innovative methods of housing construction, technical regulation, protection of the domestic market,in conducting in priority areas, training of highly qualified scientists and engineers, the formation of the information environment